(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Respiratory distress syndrome (RDS) or hyaline membrane disease (HMD) is an acute lung disease of the newborn caused by surfactant deficiency. It is Seen primarily in neonates younger than 36-38 weeks of gestational age weighing less than 2500 gram. Objective:To find out the incidence, main risk factors of HMD, note the changes in serum calcium, potassium and sodium and to study the outcome of HMD during the period of the illness. Methods: A prospective study was performed on one hundred neonate admitted to the neonatal care unit in Al-Kadhimiya Teaching Hospital. Sex, gestational age, weight, mode of delivery, maternal illnesses were studied as risk factors. Serum calcium, Na and K were measured. Results:The incidence of RDS was 0.75% of total live births, 98(98%) of them were below 2.499 kilograms and less than 37 weeks of gestational age. Risk factors of RDS are male sex accounted for 61% of total cases. Cesarean sections were 28% of the total. Maternal diabetes mellitus represented 25%. Perinatal asphyxia was 22%. Familial predisposition had an incidence of 8% and finally prolonged rupture of membranes stood for 5%. Hypocalcaemia and hypokalemia were common with serum sodium was within the lower normal limits. The time of improvement for most babies (about 40%) was by day 4 of life. Mortality was 30% with the major percentage of death (which was 90%) was between day 1 and day 4. Conclusion: RDS occurs predominantly in premature babies as a main risk factor with male sex and cesarean sections. In addition to other risk factors such as maternal diabetes mellitus and perinatal asphyxia. Associated changes in serum electrolytes and serum calcium including hypocalcaemia, hypokalemia and lower normal serum sodium are common. The 4th day of life was the time of improvement for most babies while most of them who died did so by the first 4 days of life. Among the admitted babies, about third of them (actually 30%) died because of RDS. Key words: RDS, Gestational age, Mortality.